Glial activation colocalizes with structural abnormalities in amyotrophic lateral sclerosis. (13th December 2016) - Alshikho, Mohamad J.; Zürcher, Nicole R.; Loggia, Marco L.; Cernasov, Paul; Chonde, Daniel B.; Izquierdo Garcia, David; Yasek, Julia E.; Akeju, Oluwaseun; Catana, Ciprian; Rosen, Bruce R.; Cudkowicz, Merit E.; Hooker, Jacob M.; et al.
Abstract : Objective: In this cross-sectional study, we aimed to evaluate brain structural abnormalities in relation to glial activation in the same cohort of participants. Methods: Ten individuals with amyotrophic lateral sclerosis (ALS) and 10 matched healthy controls underwent brain imaging using integrated MR/PET and the radioligand [ 11 C]-PBR28. Diagnosis history and clinical assessments including Upper Motor Neuron Burden Scale (UMNB) were obtained from patients with ALS. Diffusion tensor imaging (DTI) analyses including tract-based spatial statistics and tractography were applied. DTI metrics including fractional anisotropy (FA) and diffusivities (mean, axial, and radial) were measured in regions of interest. Cortical thickness was assessed using surface-based analysis. The locations of structural changes, measured by DTI and the areas of cortical thinning, were compared to regional glial activation measured by relative [ 11 C]-PBR28 uptake. Results: In this cohort of individuals with ALS, reduced FA and cortical thinning colocalized with regions demonstrating higher radioligand binding. [ 11 C]-PBR28 binding in the left motor cortex was correlated with FA ( r = −0.68, p < 0.05) and cortical thickness ( r = −0.75, p < 0.05). UMNB was correlated with glial activation ( r = +0.75, p < 0.05), FA ( r = −0.77, p < 0.05), and cortical thickness ( r = −0.75, p < 0.05) in the motor cortex. Conclusions: Increased uptake of the glial marker [ 11 C]-PBR28 colocalizes with changes in FA and cortical thinning. This suggests a link between disease mechanisms (gliosis and inflammation) and structural changes (cortical thinning and white and gray matter changes). In this multimodal neuroimaging work, we provide an in vivo model to investigate the pathogenesis of ALS.